The Effects of Native Advertising Disclosure and Advertising Recognition on Perceptions of News Story and News Website Credibility: A Consumer Neuroscience Approach - Mule, Jessica Loko (School of Management Studies, 2021)
The use of Native Advertising has sparked ethical concerns, due to its controversial nature inherent in its definition - a paid form of advertising that disguises persuasive communications as the editorial content of the publishing media outlet. The growing popularity of Native Advertising practices over the past decade in online news publishing has contributed towards the increasingly blurred lines between commercial and editorial content which in turn engenders feelings of deception in consumers and threatens to lower the trustworthiness of news publishers as an objective source. Therefore, the purpose of this study was to undertake theory testing guided by the tenets of the Persuasion Knowledge Model [PKM] (Friestad & Wright, 1994) to uncover insights on whether disclosure serves as an effective measure in publishers' efforts of mitigating the potential of consumer deception. In particular, this study investigated the relationships between: (1) effect of disclosure label positioning on advertising recognition; (2) mediating influence of visual attention on the aforementioned relationship; and (3) effect of advertising recognition on Inference of Manipulation [IMI] and perceptions of the online news publishers' credibility. The study used a quantitative multi-methodology research approach. An innovative Neuromarketing approach was undertaken through a psychophysiological-based analysis of visual attention to disclosure, measured as Fixation (ms/m) using eye-tracking technology, in addition to self-reported measures obtained via an online survey. In line with similar past studies, this study used convenience non-probability sampling and random assignment of participants to experimental groups, on a sample of 87 students between the ages of 20-29 years from the University of Cape Town (UCT). Findings showed no significant difference in the likelihood of advertising recognition, neither between the groups presented with a disclosure and those not, nor between the varying positions of disclosure. Additionally, advertising recognition had a positive influence on perceptions of credibility, contrary to theory and evidence from past studies (described in the Literature Review). Thus, it was concluded that disclosure and advertising recognition are necessary antecedents for critical processing and formation of judgement, but by themselves are not sufficient for perceived transparency and subsequent evaluations of the publisher's credibility. This study presents design implications for practitioners in the online news publishing industry and marketers: the perceived utility of the sponsored content, along with sponsorship transparency through disclosure, plays an important role in minimizing the negative influence of advertising recognition on perceived credibility.